Mystery of the moss-covered mansion. - Keene, Carolyn (New York, Grosset & Dunlap, 1971)
Nancy Drew sets out to prove that her father's client was unjustly accused of trying to sabotage the United States space program.
Keywords: Mystery and detective stories